2010
DOI: 10.1136/emj.2009.073460
|View full text |Cite
|
Sign up to set email alerts
|

Endotracheal intubation using a GlideScope video laryngoscope by emergency physicians: a multicentre analysis of 345 attempts in adult patients

Abstract: The GVL was not used frequently by EPs during the initial two years after its introduction. Although the GVL provides a better glottic view, the overall success rates were similar to a CL. The GVL may be useful in patients with difficult airway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 9 publications
0
28
0
Order By: Relevance
“…This results in large variation of reported prehospital intubation success rates with conventional laryngoscopy that range from only 80% up to >95% 2 14 15. Therefore, to improve visualisation of the airway, and increase overall intubation success and subsequent patient safety, videolaryngoscopy in the prehospital setting has become an evolving field; however, most of the studies published are performed on manikins, simulating prehospital conditions 16 17.…”
Section: Discussionmentioning
confidence: 99%
“…This results in large variation of reported prehospital intubation success rates with conventional laryngoscopy that range from only 80% up to >95% 2 14 15. Therefore, to improve visualisation of the airway, and increase overall intubation success and subsequent patient safety, videolaryngoscopy in the prehospital setting has become an evolving field; however, most of the studies published are performed on manikins, simulating prehospital conditions 16 17.…”
Section: Discussionmentioning
confidence: 99%
“…Operators using the GVL were able to consistently obtain good CL views, suggesting that they were able to visualize the glottic opening, but were unable to successfully complete the intubation because they had difficulty maneuvering the tracheal tube to the glottic inlet [11]. Prior studies have demonstrated that using the GVL results in uniformly excellent views of the glottis, but this does not necessarily correlate with intubation success [2,12,13]. The steep curvature of the GVL blade allows easy visualization of the vocal cords, but this shape requires that the operator navigate the tube along this steep curvature up toward the glottic opening (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, its use has become increasingly common for emergency intubations [1][2][3][4][5]. Previous research has evaluated the performance of the GVL, comparing it to other intubation devices, including the direct laryngoscope (DL) [2,3,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The risks compound further when inexperienced providers are responsible for securing the airway under such challenging conditions. Consequently, there is an increased rate of complications during urgent endotracheal intubation compared with intubations in the operating room 10,11 . Airway management in the emergency department is therefore a major challenge because of both challenging patient conditions and variability in the provider's airway management skills.…”
Section: Challenges In the Use Of Video Laryngoscopementioning
confidence: 99%
“…The Accreditation Council for Graduate Medical Education (ACGME) states that critical care trainees "must demonstrate competence in procedural and technical skills in airway management and endotracheal intubation" 19 . Such skills in urgent endotracheal intubation are typically gained in the ICU, where almost all intubations are high-risk events due to the urgency in securing the airway 3,10 . Consequently, there is an increased rate of complications associated with tracheal intubations in the ICU setting compared with intubations in the operating room 4 .…”
Section: Intubation In Intensive Care Unitmentioning
confidence: 99%